1993
DOI: 10.1002/ajmg.1320460512
|View full text |Cite
|
Sign up to set email alerts
|

Precise mapping of a de novo duplication 18(q21→q22) utilizing cytogenetic, biochemical, and molecular techniques

Abstract: We describe the first de novo inverted duplication of 18q. Due to the difficulty of identifying de novo chromosome abnormalities based solely on cytologic studies, precise definition of the 18q duplication was attempted by integrating cytogenetic and clinical findings with biochemical and molecular dosage studies. The combined results demonstrated that the proposita had a duplication of 18q21-->q22 with a karyotype of 46,XX,-18, + inv dup(18) (pter-->q12.1::q22-->q21::q12.1-->qter). The duplication of this spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Attempts at karyotype-phenotype correlations based on a limited number of unrelated patients with (almost) similar chromosomal imbalances have often been unsuccessful and therefore must be viewed with caution (Wilson et al 1990). Triplicated chromosomal segments appear not to be autonomous in producing the phenotypic manifestations (Wilson et al 1990;Mewar et al 1993;Wolff et al 1993;Boghosian-Sell et al 1994). To our knowledge, only seven patients with duplications of the proximal region of the long arm of chromosome 18 have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Attempts at karyotype-phenotype correlations based on a limited number of unrelated patients with (almost) similar chromosomal imbalances have often been unsuccessful and therefore must be viewed with caution (Wilson et al 1990). Triplicated chromosomal segments appear not to be autonomous in producing the phenotypic manifestations (Wilson et al 1990;Mewar et al 1993;Wolff et al 1993;Boghosian-Sell et al 1994). To our knowledge, only seven patients with duplications of the proximal region of the long arm of chromosome 18 have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…In these cases patients display manifestations ranging from a relatively mild to a severe phenotype. Genotype-phenotype correlations have suggested that duplication of regions (18)(q12.1q21.2) is critical for the trisomy 18 phenotype [9,10], while the relationship between duplication of the other 18q regions and mental retardation, growth delay, and dysmorphism is less clear. Our patient displayed only mild dysmorphic features and speech delay.…”
Section: Discussionmentioning
confidence: 99%
“…Duplications of 18q21 ! 18q22 give rise to a mild phenotype [Wolf et al, 1993] in comparison to other 18q duplications [Erlich et al, 1983]. To this date, no duplication of 18q has been reported involving only 18q23 !…”
Section: Introductionmentioning
confidence: 97%